2010
DOI: 10.1212/wnl.0b013e3181f96175
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of facioscapulohumeral muscular dystrophy 2

Abstract: Clinically, patients with FSHD2 are indistinguishable from patients with FSHD1. The present data suggest that FSHD1 and FSHD2 are the result of the same pathophysiologic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
144
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(154 citation statements)
references
References 23 publications
7
144
2
1
Order By: Relevance
“…2,3 A small percentage of FSHD subjects (FSHD2) show the FSHD muscle weakness pattern but do not have a contracted 4q D4Z4 array. 4 Recent work has suggested that both types of FSHD are characterized by expression and stabilization of mRNA produced from an open reading frame in the most telomeric D4Z4 repeat that encodes a potentially toxic protein: a long isoform of DUX4. 3,5,6 Weakness in FSHD appears to be of myogenic, rather than neurogenic, origin.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 A small percentage of FSHD subjects (FSHD2) show the FSHD muscle weakness pattern but do not have a contracted 4q D4Z4 array. 4 Recent work has suggested that both types of FSHD are characterized by expression and stabilization of mRNA produced from an open reading frame in the most telomeric D4Z4 repeat that encodes a potentially toxic protein: a long isoform of DUX4. 3,5,6 Weakness in FSHD appears to be of myogenic, rather than neurogenic, origin.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the mother (385-102), the size of her permissive allele (27 units) might explain why she is not affected with FSHD, despite her SMCHD1 variant and D4Z4 hypomethylation. In 2010, de Greef et al 4 showed that the average size of the shortest permissive allele in FSHD2 is 16 units, which is much shorter than the average of 28 units found in control individuals, which was confirmed in a later study. 4,21 The permissive allele in the proband (385-203) and his mother (385-102) is 27 units, relatively long for FSHD2.…”
Section: A a T T A A A G T A A G T A T C T A A T T A A A G T A A G T mentioning
confidence: 74%
“…3 The genetic forms identified thus far, FSHD1 and FSHD2, are clinically indistinguishable. 4 Both forms are associated with partial chromatin relaxation of the D4Z4 macrosatellite repeat array on the subtelomere of the long arm of chromosome 4 and transcriptional derepression of the D4Z4 unit-encoded DUX4 retrogene in skeletal muscle. [5][6][7][8][9] DUX4 is a germ line transcription factor that is normally repressed in somatic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Although FSHD1 and FSHD2 have different underlying genetic defects, they both appear to be caused by transcriptional derepression of DUX4 in skeletal muscle. 11 The contraction of D4Z4 repeats in FSHD1 is associated with partial demethylation of the shortened allele, and relaxation of the local chromatin structure, whereas, in FSHD2, global genomic demethylation is observed.…”
Section: Discussionmentioning
confidence: 99%